2017
DOI: 10.15446/agron.colomb.v35n2.62875
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between crop nutritional status, spectral measurements and Sentinel 2 images

Abstract: RESUMENIn order to monitor the nutritional status of some crops based on plant spectroscopy and Sentinel 2 satellite images in Colombia, spectral reflectance data were taken between 350 and 2,500 nm with a FieldSpec 4 spectrometer in rubber, rice, sugar cane, maize, soybean, cashew, oil palm crops, pastures and natural savanna. Furthermore contents of mineral nutrients in leaves were determined. Several vegetation indexes and red edge positions were calculated using various methods from spectral data and Senti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
10
0
4
Order By: Relevance
“…Una probable explicación del bajo rendimiento del MTCI en este trabajo, es que el ancho de las bandas 4 y 6 de las imágenes S-2 se encuentran fuera del rango óptimo para su estimación. El NDVI presentó un R 2 de 0.60, menor al encontrado por Martínez (2017), quien reportó un R 2 de 0.65 al relacionar dicho índice con el CND. Su bajo rendimiento se debe al efecto de saturación que se da a partir de un CND de 4 g m -2 (Schlemmer et al, 2013).…”
Section: Estimación Del Contenido De Nitrógeno Del Doselunclassified
See 1 more Smart Citation
“…Una probable explicación del bajo rendimiento del MTCI en este trabajo, es que el ancho de las bandas 4 y 6 de las imágenes S-2 se encuentran fuera del rango óptimo para su estimación. El NDVI presentó un R 2 de 0.60, menor al encontrado por Martínez (2017), quien reportó un R 2 de 0.65 al relacionar dicho índice con el CND. Su bajo rendimiento se debe al efecto de saturación que se da a partir de un CND de 4 g m -2 (Schlemmer et al, 2013).…”
Section: Estimación Del Contenido De Nitrógeno Del Doselunclassified
“…Con respecto al IRECI, dicho índice mostró valores de R 2 de 0.91, mayor al R 2 = 0.73 encontrado por Martínez (2017) en diferentes cultivos. Asimismo, con el Cl Red-edge se obtuvo un R 2 de 0.93, en tanto que, en maíz, Schlemmer et al (2013) reportaron un R 2 de 0.87 y González-Piqueras et al (2017) un R 2 de 0.91 en trigo.…”
Section: Estimación Del Contenido De Nitrógeno Del Doselunclassified
“…Sentinel-2 satellites have a 5-day revisit cycle, increasing the chance of obtaining cloud-free images at the necessary crop growth stage for the study sites. There has been much research interest in the use of Sentinel-2 data in agriculture to study crop nutrient status, biophysical variables and soil mapping in the local, regional and global scale [23][24][25][26]. There is also a potential to map sub-paddock variability and provide an indication of crop yield before harvest using Sentinel-2 data.…”
Section: Remote Sensing Imagerymentioning
confidence: 99%
“…Informes anteriores han documentado la capacidad de los índices vegetativos para estimar el potencial de rendimiento de la caña de azúcar, sin embargo, la mayoría de ellos se ha centrado en el uso de plataformas basadas en satélites o sensores pasivos (Lofton et al, 2012;Zhao et al, 2016;Johansen et al, 2017;Martínez, 2017) y muy pocos en demostrar la capacidad de un sensor remoto activo en tierra para estimar variables de interés agrícola en campos de caña de azúcar en zonas tropicales.…”
Section: Vegetation Indexesunclassified
“…Previous research works have documented the capability of vegetation indexes to estimate the potential crop yield of the sugarcane; nevertheless, most of them have been focused on the use of satellite and passive sensors platforms (Lofton et al, 2012;Zhao et al, 2016;Johansen et al, 2017;Martínez, 2017)and very few have demonstrated the ability of an active remote sensor on the ground to estimate variables of interest in a sugarcane crop located in a tropical zone.…”
Section: Introductionmentioning
confidence: 99%